Validation of an XCT/fDOT System on Mice. (12th April 2012) - Koenig, Anne; Planat-Chrétien, Anne; Hassler, Kai; Bucher, Martina; Coutard, Jean-Guillaume; Hervé, Lionel; Brambilla, Marco; Josserand, Véronique; Coll, Jean-Luc; Vats, Divya; Dikaiou, Katerina; Rudin, Markus; et al.
Abstract : In this paper we present systems for dual modality imaging, combining fluorescence-enhanced diffuse optical tomography and X-ray computed tomography. Fluorescence diffuse optical tomography is carried out in a cylindrical geometry, which ensures optimal sampling and a straight forward integration with the X-ray modality. Specific acquisition protocols and reconstruction software have been developed to this end. The X-ray computed tomography serves two purposes. First, it provides the anatomical information in the registered dual modality images. Second, it provides the actual shape and boundaries of the animal as a priori input to the fluorescence reconstruction algorithm. To evaluate the performance of the optical imaging system, experiments have been conducted on phantoms, mice with inserted fluorescing capillaries, and finally on mice bearing tumors, ex-vivo and in-vivo . Experiments on mice with capillaries inserted in different region of interest, allow estimating the detection limits of fluorophore concentrations. The fluorescence reconstructions are shown to be geometrically consistent with the X-ray images. Finally we demonstrate the capability of the bimodal system to localize real tumours in mice in-vivo . These results show that dual modality fluorescence-enhanced diffuse optical tomography and X-ray computed tomography imaging in cylindrical geometry has a high potential for small animal tumour evolution studies.